2021
DOI: 10.3389/fonc.2021.666624
|View full text |Cite
|
Sign up to set email alerts
|

Are Molecular Alterations Linked to Genetic Instability Worth to Be Included as Biomarkers for Directing or Excluding Melanoma Patients to Immunotherapy?

Abstract: The improvement of the immunotherapeutic potential in most human cancers, including melanoma, requires the identification of increasingly detailed molecular features underlying the tumor immune responsiveness and acting as disease-associated biomarkers. In recent past years, the complexity of the immune landscape in cancer tissues is being steadily unveiled with a progressive better understanding of the plethora of actors playing in such a scenario, resulting in histopathology diversification, distinct molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 124 publications
(168 reference statements)
0
2
0
1
Order By: Relevance
“…Although microsatellite instability-high (MSI-H) tumors commonly have a high TMB, the converse is not true. 22 While most melanomas do have a high TMB, the frequency of MSI-H is much lower. In a small study, only 11% of 56 primary cutaneous melanomas and 21% of 42 metastatic melanomas were MSI-H. 23 Mismatch repair protein deficiency (dMMR) has been reported in around 13% of cutaneous melanomas, with pathologically-relevant MMR deficiency rates of <1% for uveal melanoma.…”
Section: Microsatellite and Mismatch Repair Statusmentioning
confidence: 99%
“…Although microsatellite instability-high (MSI-H) tumors commonly have a high TMB, the converse is not true. 22 While most melanomas do have a high TMB, the frequency of MSI-H is much lower. In a small study, only 11% of 56 primary cutaneous melanomas and 21% of 42 metastatic melanomas were MSI-H. 23 Mismatch repair protein deficiency (dMMR) has been reported in around 13% of cutaneous melanomas, with pathologically-relevant MMR deficiency rates of <1% for uveal melanoma.…”
Section: Microsatellite and Mismatch Repair Statusmentioning
confidence: 99%
“…Consistent with this theory, high TMB is generally associated with improved overall survival and immunotherapy response in melanoma patients ( 8 , 86 88 , 107 ). However, there is still some debate about a good way to make high and low TMB definitions more consistent across studies to improve its use as a biomarker for immunotherapy response [reviewed in ( 108 , 109 )]. Recent research has shown that TMB and neoantigen burden scores can predict response and likelihood of resistance to immunotherapies ( 110 ).…”
Section: Key Players In Resistance Against Immune Checkpoint Inhibito...mentioning
confidence: 99%
“…Despite recent groundbreaking advances in the treatment of cutaneous melanoma, it remains one of the most treatment-resistant malignancies [ 21 ]. Immunotherapies represent an alternative to molecular targeted therapies.…”
Section: Gimm and Immunotherapymentioning
confidence: 99%